Antioxidant potential in non-extractable fractions of dried persimmon (Diospyros kaki Thunb.). (1st July 2016) - Matsumura, Yoko; Ito, Toshihiro; Yano, Hisakazu; Kita, Eiji; Mikasa, Keiichi; Okada, Masatoshi; Furutani, Azusa; Murono, Yuka; Shibata, Mitsuru; Nishii, Yasue; Kayano, Shin-ichi
Highlights: We studied dried persimmon (extracts, non-extracted fractions) antioxidant activity. ORAC value of non-extracted fraction contributed highly (81.7%) to total ORAC value. Plasma ORAC values were higher in rats fed non-extracted fraction than control rats. ORAC value of non-extracted fraction rose on large bowel stage colonic fermentation. Abstract: Dried fruits of persimmon ( Diospyros kaki Thunb.) are a traditional food in Japan and contain large quantities of tannins. In this study, we investigated the in vitro and in vivo antioxidant potentials of non-extractable fractions from dried persimmons. Hydrolysed non-extractable fractions showed the highest antioxidant activities in vitro . In subsequent experiments, the plasma oxygen radical absorbance capacity (ORAC) values in rats supplemented with a 5% non-extractable fraction were approximately 1.5 times higher than those in control rats after 1 week in vivo . Furthermore, using an in vitro model of the gastrointestinal tract, the ORAC values of the non-extractable fraction were significantly increased with colonic fermentation in the large bowel stage. These data indicate that non-extractable fractions may possess significant antioxidant potential in vitro and in vivo .